2014
DOI: 10.1111/evj.12361
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the faecal microbiota of mares precede the development of post partum colic

Abstract: Foaling had minimal effects on the mares' faecal microbiota. Numerous differences in the faecal microbiota preceded colic. Associations between Firmicutes (particularly Lachnospiraceae and Ruminococcaceae) and Proteobacteria and development of colic could lead to measures to predict and prevent colic. The Summary is available in Chinese - see Supporting information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 35 publications
16
128
5
3
Order By: Relevance
“…The majority of intestinal microbes are refractory to culture and the ability to interrogate these rich and dynamic microbial communities using culture-independent methods has only recently become technically and economically feasible. Indeed, several groups have now described the composition of fecal [2531] and gastric [32] microbiota in healthy horses, as well as associations between specific conditions affecting horses (such as laminitis [22], colic [31], and colitis [33]) and characteristic changes in the fecal microbiota. That said, there are still many uncertainties regarding the healthy equine gut microbiota including the composition of the gastric and small intestinal microbiota in relation to that colonizing the cecum and colon, and the composition of mucosal communities in relation to the luminal contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of intestinal microbes are refractory to culture and the ability to interrogate these rich and dynamic microbial communities using culture-independent methods has only recently become technically and economically feasible. Indeed, several groups have now described the composition of fecal [2531] and gastric [32] microbiota in healthy horses, as well as associations between specific conditions affecting horses (such as laminitis [22], colic [31], and colitis [33]) and characteristic changes in the fecal microbiota. That said, there are still many uncertainties regarding the healthy equine gut microbiota including the composition of the gastric and small intestinal microbiota in relation to that colonizing the cecum and colon, and the composition of mucosal communities in relation to the luminal contents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies applying next-generation sequencing methods to healthy equine hindgut samples have detected Firmicutes -dominated microbial profiles, followed in relative abundance by some combination of Bacteroidetes , Proteobacteria , or Verrucomicrobia as the second and third most prevalent phyla, depending on the study [22, 26, 31, 33]. In all of these studies, bacteria in the phylum Firmicutes outweighed the next most common phylum by a ratio of 4:1 or greater, in contrast to the present data wherein the Firmicutes to Bacteroidetes ratio was approximately 1:1 in all horses.…”
Section: Discussionmentioning
confidence: 99%
“…In horses, the intestinal microbiota can be modified by various factors, such as gastrointestinal diseases [1], changes in diet [2], the use of antibiotics [3,4] and general anesthesia [5]. A recent study found that changes in the intestinal microbiota might predict the development of postpartum gastrointestinal disease [6], indicating that alterations in the microbiota resulting from various physiological events might alter the risk of subsequent disease. Recent studies using genetic sequencing techniques reported that exercise modified the structure of the intestinal microbiota in mice [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…10 Another area of research that is providing exciting new ideas about why colic develops and how some forms might be prevented in the future are investigations into the equine gut microbiome, such as the relationship between the gut microbiota and large colon torsion in brood mares. 11 While microbiome studies are expensive and limited funds are available, further research in this area is important.…”
Section: Finding Something Newmentioning
confidence: 99%